FIDIC users' guide - Barr, Brian; Grutters, Leo (ICE Publishing, 2013)
'FIDIC Users' Guide' focuses on the practical administration of the Federation Internationale des Ingenieurs-Conseils (FIDIC) Conditions of Contract for Construction and the Conditions of Contract for Plant & Design-Build, a revised family of Conditions of Contract published in 1999 to address the increasing size and complexity of construction projects.